Cloning and expression in Escherichia coli and Bacillus subtilis of the hemolysin (cereolysin) determinant from Bacillus cereus. - Kreft, J (1983)
From a cosmid gene bank of Bacillus cereus GP4 in Escherichia coli we isolated clones which, after several days of incubation, formed hemolysis zones on erythrocyte agar plates. These clones contained recombinant cosmids with B. cereus DNA insertions of varying lengths which shared some common restriction fragments. The smallest insertion was recloned as a PstI fragment into pJKK3-1, a shuttle vector which replicates in Bacillus subtilis and E. coli. When this recombinant plasmid (pJKK3-1 hly-1) was transformed into E. coli, it caused hemolysis on erythrocyte agar plates, but in liquid assays no external or internal hemolytic activity could be detected with the E. coli transformants. B. subtilis carrying the same plasmid exhibited hemolytic activity at levels comparable to those of the B. cereus donor strain. The hemolysin produced in B. subtilis seemed to be indistinguishable from cereolysin in its sensitivity to cholesterol, activation by dithiothreitol, and inactivation by antibodies raised against cereolysin. When the recombinant DNA carrying the cereolysin gene was used as a probe in hybridization experiments with chromosomal DNA from a streptolysin O-producing strain of Streptococcus pyogenes or from listeriolysin-producing strains of Listeria monocytogenes, no positive hybridization signals were obtained. These data suggest that the genes for these three SH-activated cytolysins do not have extended sequence homology.